Enhancing student learning, participation and accountability in undergraduate group projects through peer assessment - Subramanian, Rajesh; Lejk, Mark (South African Journal of Higher Education, 2016)
This paper reports a study undertaken on undergraduate student group projects at Botho College, Botswana. At the College group projects are assessed entirely by the supervising tutor. This has led to some dissatisfaction on the part of students and staff when students’ contributions to the project are unequal and this is not recognised in the assessment. To overcome this, a trial was conducted in which a group of students performed peer assessment of the contributions of individual group members to the project. These assessments were compared to tutor assessments. The results are discussed together with feedback from students and staff and the implications for Botho College and higher education in general are examined.